Surface immobilisation of antibody on cyclic olefin copolymer for sandwich immunoassay - Raj, J.; Herzog, G.; Manning, M.; Volcke, C.; MacCraith, B.; Ballantyne, S.; Thompson, M.; Arrigan, Damien (Elsevier, 2009)
In this work, the surface functionalisation of the commercially available cyclic olefin copolymer (COC)materials, ZeonorR and ZeonexR, has been studied. The methodology employed involved oxidation inoxygen plasma, functionalisation of the oxidized surface with aminopropyl triethoxy silane and, finally,attachment of antibody using covalent linker molecules. 1,4-Phenylene diisothiocyanate was selected asthe most suitable cross-linker for the attachment of protein, as assessed by fluorescent intensity measurementson immobilised FITC-labelled IgG antibody. The modification methodwas characterised by contactangle measurements, ellipsometry, X-ray photoelectron spectroscopy (XPS) and fluorescence microscopy.The data are consistent with the deposition of a polymeric film of the silane chemisorbed to the oxidisedplastic surface. The functionalised surfaces were employed in a sandwich immunoassay format usingthe reagents goat anti-human IgG (GHIgG) and fluorescently labelled GHIgG (Cy5-GHIgG) as captureand detection antibodies, respectively, and with human IgG (HIgG) as the model analyte. The lowestconcentration of HIgG detected was 0.1 ng ml-1, with a relative standard deviation of 15%. Non-specificbinding effectswere also assessed. The method and supporting data demonstrate that simple approachesto surface functionalisation can be adapted to plastic-based devices.